Integration of Education and Modern Socio Political and Economic Trends in The World (International Journal of Scientific Trends, 2024)
At the present stage of fundamental reform of our society, it becomes clear that integration processes in the field of education are directly related to similar processes in economics and politics. Integration of education is a problem that the world community is just beginning to solve. It is multidimensional and requires a step-by-step solution.